Membumikan Kopi sebagai Komoditas Unggulan dan Sumber Penghidupan Berkelanjutan Masyarakat di Desa Patikalain Kabupaten Hulu Sungai Tengah - Enjella, Nadia; Khairussalam; Fahma, Erisa Nur; Khairunnisa, Syifa; Kimil, Muhammad Rezky; Risna; Zhafirah, Haura; Tasti, Adinda Nur; Nabilah, ⁠Yashna; Asrariah, Siti; Zulhidan, ⁠Muhammad Royyan; Adnyana, I Kadek Ukir Dwi (Hayak Bamara: Jurnal Pengabdian Masyarakat, 2025)
The village of Patikalain, Hantakan Subdistrict, Hulu Sungai Tengah Regency, has great potential for coffee commodity development, particularly robusta coffee, thanks to its favorable geographical and climatic conditions. However, the village community still faces various challenges, such as limited infrastructure, access to modern agricultural technology, and a lack of knowledge regarding post-harvest processing techniques. This community service program aims to maximize the potential of coffee as a flagship commodity through community empowerment using a live-in approach, conducted from July 23 to September 4, 2024. The community service team resides in the village to gain a deep understanding of the social and economic conditions of the community. The solutions implemented include coffee cultivation training, post-harvest processing, and the formation of active coffee farmer groups, as well as establishing partnerships with buyers to expand market access. Achievements include improved community understanding of coffee cultivation, increased production, and higher farmer incomes. However, inadequate infrastructure and limited access to technology remain challenges for further development. Developing coffee as a commodity in Patikalain Village requires a comprehensive approach with government and institutional interventions, such as regular training, technology access, and improvements to distribution and marketing channels for farm products. This study explores the potential of coffee in Patikalain Village, analyzes the challenges faced, and identifies optimal strategies for developing coffee as a flagship commodity. It is hoped that the results of this study will serve as a foundation for further collaboration between the government, institutions, and farmers to maximize the potential of coffee as a sustainable source of livelihood for the village community.